Pengaruh Financial Restructuring Terhadap Bondholder Wealth: Sebuah Tinjauan Teoritis - Christian Herdinata (BIP's JURNAL BISNIS PERSPEKTIF, 2012)
Many of the spectacular surge in the restructuring of companies around the world. Restructuring activities largely focused on improving the efficiency of companies through financial restructuring. Financial restructuring of the view that the decision may lead to redistribution of wealth between shareholders andcreditors (bondholder) has been widely discussed since the Black and Scholes (1973), but the change in capital structure as a result of financial restructuring affects bondholder wealth has not been much discussed. Financial restructuring that occurs through changes incorporate capital structure, for example: leveragedbuy-out (LBO), leveraged recapitalizations (LRs), buy back shares, or employee stock ownership plans (ESOPs) that affect the wealth of bondholders to be interesting to study. The expected outcome of this research is to give a comprehensive overview of a theoretical and empirical review of how financial restructuring affects bondholder wealth.